Integration of Transcriptomics and Metabolomics Reveals that Salicylic Acid Alleviates Postharvest Chilling Injury in Plum Fruit by Regulating Lipid Metabolism - GUO Nan, XIAO Guofang, QIAO Ting, YANG Yang (Shipin Kexue)
In this study, we investigated the potential mechanism through which salicylic acid (SA) reduces chilling injury (CI) index in plum fruit from the perspective of lipid metabolism. The effects of exogenous SA treatment on CI index, CI incidence, electrolyte permeability, malondialdehyde (MDA) content, lipoxygenase activity, and membrane lipid fatty acid unsaturation index plum fruit stored at 0 ℃ were evaluated, and transcriptomic and metabolomics analyses were conducted on the fruit stored for 18 days. The results showed that SA alleviated CI by inhibiting membrane lipid degradation, mitigating membrane lipid peroxidation, and regulating endogenous jasmonic acid synthesis in plum fruit during cold storage. Ethylene responsive factor (ERF) was potentially involved in this process. The above results demonstrate that the alleviation of chilling injury by SA is closely related to its inhibitory effect on membrane lipid degradation and oxidative injury and its regulatory effect on the key genes in the jasmonic acid synthesis pathway.